The economic impact of stroke in The Netherlands: the €-restore4stroke study - van Eeden Mitchel; van Heugten Caroline M; Evers Silvia MAA (BMC, 2012)
Abstract Background Stroke has a considerable socio-economic impact worldwide and is the leading cause of disabilities in the Western world. Economic studies of stroke focus merely on physical aspects and clinical interventions. To our current knowledge there is no comprehensive economic study investigating the economic impact of stroke including psychological and social aspects. The €-Restore4Stroke project, part of a large comprehensive research programme Restore4Stroke, aims to investigate the total economic impact of stroke in the Netherlands. Methods Two trial-based economic evaluation studies will be conducted within the €-Restore4Stroke project: one focussing on a self-management intervention and one on an augmented cognitive behavioural therapy intervention. Both include cost-effectiveness analyses and cost-utility analyses as primary research methods. Furthermore, a cost-of-illness study investigating costs after stroke attached to a cohort study and a record linkage study in which four databases are linked to investigate patterns of health care consumption before and after stroke, are embedded in €-Restore4Stroke. All studies will be performed from a societal perspective. The primary outcome measure for the cost-effectiveness analysis is the increase in health status on the primary outcome scales. Within the cost-utility analysis, the primary outcome measure is quality-adjusted life years (QALYs) for which an indirect preference-based technique will be used. In the self-management study we will also look at the estimation of health effects on informal caregivers. Cost outcomes in the cost-of-illness study will be computed with a cost questionnaire and linkage of several databases will be used to derive outcomes in the record linkage study, Discussion €-Restore4Stroke will provide new insights and evidence for the economic impact of psychosocial consequences after stroke. Besides being innovative in various ways (i.e. focussing on the chronic phase after stroke and including personal factors as possible determinants of long-term re-integration including quality of life in a prospective longitudinal design), a major strength of €-Restore4Stroke is that we include impact on informal caregivers. The outcomes of this study will provide health care decision makers with valuable and necessary information regarding stroke care related decisions. Trial registration NTR3051 (RCT Self-management), NTR2999 (RCT Augmented Cognitive Behavioural Therapy)